2021
DOI: 10.1186/s40794-021-00150-6
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic stroke following snake bite in Burkina Faso (West Africa). A case series

Abstract: Background Snake bites remain a major medical problem in West Africa, and hemorrhagic stroke following a snakebite has emerged as a rare secondary condition. The objective of this study was to determine the neurological complications following snake bite. Methods This study included all the cases of hemorrhagic stroke following snake bite admitted in the neurology Department of Yalgado Ouedraogo University Teaching Hospital during the period from J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
2
0
2
Order By: Relevance
“…Towards this end, Feola et al reported 2.6% of patients with cerebrovascular complications among 309 snakebite victims 9. Ischaemic stroke has also been reported in various snake envenomation 16–21. Gawarammana et al found 1.8% ischaemic stroke cases in 500 viper bite patients 22.…”
Section: Discussionmentioning
confidence: 99%
“…Towards this end, Feola et al reported 2.6% of patients with cerebrovascular complications among 309 snakebite victims 9. Ischaemic stroke has also been reported in various snake envenomation 16–21. Gawarammana et al found 1.8% ischaemic stroke cases in 500 viper bite patients 22.…”
Section: Discussionmentioning
confidence: 99%
“…Les complications neurologiques ne sont généralement rapportées dans la littérature que sous forme de cas cliniques. Dabilgou et al [ 6 ] ont rapporté 3 cas d’hémorragies cérébrales post envenimation à Ouagadougou, et Yalcouyé et al [ 27 ] ont décrit un cas d’hémorragie cérébrale avec cécité irréversible à Bamako. Les études sur de grandes populations sont rares en Afrique et ne sont pas précises quant aux complications neurologiques.…”
Section: Discussionunclassified
“…Le saignement est dû à une lésion vasculaire induite par le venin et est entretenu par d’autres mécanismes en lien avec le venin tels que la thrombopénie, la coagulopathie de consommation, la défibrination et l’hyperfibrinolyse [ 15 ]. Cette coagulopathie a été rapportée par Dabilgou et al [ 6 ] avec une élévation des D-dimères à 7 500 mg/l chez un patient, une thrombopénie et une diminution du taux de prothrombine chez un autre. C’était également le cas de Yalcouyé et al [ 27 ] dont le patient avait une thrombopénie et un sang complètement incoagulable au test de coagulation sur tube sec réalisé à l’admission.…”
Section: Discussionunclassified
“…to quality antivenom serum is frequently limited [4,7]. Most studies conducted in Burkina Faso have focused on the prevalence or incidence of snakebites [6,8,9], while recent research on complications has been case reports from referral hospitals [10][11][12]. Few studies have explored both the complications of snakebite envenomation and the associated factors.…”
Section: Introductionmentioning
confidence: 99%